CSIG-05. TRPM7 INDUCES MECHANISTIC TARGET OF Rap1b THROUGH DOWNREGULATION OF miR-28-5p IN GLIOMA PROLIFERATION AND INVASION. (11th November 2019) - Wan, Jingwei; Guo, Alyssa; Liu, Mingli
Abstract: Our previous findings demonstrate that TRPM7 is critical in regulating human glioma tumorigenesis. miRNA participate in complex regulatory networks that may affect almost every cellular and molecular processes in glioma formation and progression, because a specific miRNA may simultaneously regulate many targets; While, a single protein target can be regulated by different miRNAs. Here, we explored the role of miRNAs in the progression of human gliomas by comparing miRNA expression profiles due to differentially expressed TRPM7. We determined 1) miRNA targets of TRPM7 by miroRNA microarray analysis upon TRPM7 silencing in glioma cell lines. 2) whether TRPM7 regulates glioma cell proliferation (MTT) and migration/invasion (transwell invasion assay) through different functional domains by transfecting wild-type human TRPM7 (wtTRPM7) or constructs with the α-kinase domain deleted (Δkinase) or with a point mutation within the ATP binding site of the α-kinase domain (K1648R-KR) into glioma cells. 3) the roles of miR-28-5p in glioma tumorigenesis by over- or under-expressing miR-28-5p in vitro . 4) whether Rap1b is a target of miR28-5p and the role of Rap1b in glioma tumorigenesis. 5) whether Rap1b can counteract the miR28-5p function on glioma tumorigenesis. We found 1) a list of 16 downregulated and 10 upregulated miRNAs that are statistically significant with fold changes greater than 2 by TRPM7 knock-down by miRNA microarray, and miR-28-5p as a promising candidate for functional analyses. 2) cell invasion was significantly reduced in Δkinase or K1648R transfectants, indicating that TRPM7 kinase activity is required for glioma cell migration/invasion. 3) overexpression of miR-28-5p caused a significant decrease in cell proliferation and migration by targeting Rap1b. 4) Co-transfection with siRap1b with miR28-5p inhibitor reduced the glioma cell proliferation and invasion caused by the latter. In summary, TRPM7 induces mechanistic target of Rap1b through downregulation of miR-28-5p in glioma proliferation and invasion.